Navigating challenges on the path to net zero emissions: A comprehensive review of wind turbine technology for implementation in Indonesia - Yudiawan Fajar Kusuma; Abid Paripurna Fuadi; Buddin Al Hakim; Cahyo Sasmito; Andi Cahyo Prasetyo Tri Nugroho; Muh Hisyam Khoirudin; Dany Hendrik Priatno; Amir Tjolleng; Ilham Bagus Wiranto; Iqbal Reza Al Fikri; Teguh Muttaqie; Aditya Rio Prabowo (Results in Engineering, 2024)
Indonesian government are actively intensifying its efforts to achieve the ambitious target of attaining 23% renewable energy consumption for electricity supply. With Indonesia, its vast coastline and abundant wind resources, has enormous potential for developing offshore wind energy. As a result, floating offshore wind turbines (FOWTs) have become a promising solution to harness the wind energy potential in deeper waters. This paper aims to provide a comprehensive analysis of the trends and challenges associated with Floating Offshore Wind Turbines (FOWTs), especially in Indonesia. A study of existing FOWTs technologies in the world was done to compare all advantages and disadvantages and the implementation in Indonesia. Studies of floater technology based on numerical and experiments to optimization the suitable platform and also identify potential sites for wind energy generation. The last is determining transportation and installations FOWTs. The result revealed that there are 10 regions with wind speed potential exceeding 5 m/s, with three areas having the best average energy capacity potential. The FOWTs floater platform designs are suitable for the depth range of 50–80 m, namely spar, semisubmersible, and TLP. Both the logistics and installation of offshore wind turbines are influenced by various factors such as port locations, wind farm locations, and manufacturing facilities.